2020
DOI: 10.1080/07391102.2020.1845980
|View full text |Cite
|
Sign up to set email alerts
|

In silicoscreening and molecular dynamics of phytochemicals from Indian cuisine against SARS-CoV-2 MPro

Abstract: SARS-CoV-2 cause fatal infection in 213 countries accounting for the death of millions of people globally. In the present study, phytochemicals from spices were assessed for their ability to interact with SARS-CoV-2 M Pro. Structure based virtual screening was performed with 146 phytochemicals from spices using Autodock Vina. Phytochemicals with binding energy ! À8.0 kcal/mol were selected to understand their interaction with M Pro. Virtual screening was further validated by performing molecular docking to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Our results demonstrated that the selected bioactive molecules interacted strongly with the Mpro target enzymes, affirming the stability of the target-ligand complex and providing a better association constant [26]. These findings suggest that the electrostatic interactions dominate the non-covalent interaction in the cited ligands, making them efficient in targeting Mpro.…”
Section: Discussionsupporting
confidence: 64%
“…Our results demonstrated that the selected bioactive molecules interacted strongly with the Mpro target enzymes, affirming the stability of the target-ligand complex and providing a better association constant [26]. These findings suggest that the electrostatic interactions dominate the non-covalent interaction in the cited ligands, making them efficient in targeting Mpro.…”
Section: Discussionsupporting
confidence: 64%
“…Researchers have studied several phytochemicals to target SARS CoV-2 M pro through a similar technique. Rajendran et al (2022) [ 91 ] showed two compounds from Indian cuisine, cinnamtannin B2 and cyanin, could inhibit M pro in silico compared with the control. Similarly, natural compounds like withanoside V, and somniferine were effective against the main protease in a molecular docking experiment [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Screening of the phytochemicals, as obtained from LC-MS/MS QTOF analysis, revealed that seven phytochemicals that are present in VK have been reported previously for potential activity against SARS-CoV-2. These are 6-gingerol [22], 6-shogoal [22], Diacetoxy-4 -gingerdiol [23], gallic acid [24], magnoflorine [24], solasonine [25] and solamargine [25]. The binding site of these phytochemicals from the previous reports and the plant sources of these are summarised in Table 3.…”
Section: Screening Of Phytochemicalsmentioning
confidence: 99%